Work Environment and Compensation on Teacher Performance - Joko Suyono; Yusuf Siswanto; Arasy Alimudin; Damarsari Ratnasahara Elisabeth (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This research was conducted at SMA (Senior High School) and SMK (Vocational High School) Kawung 2 Surabaya with the aim of analyzing the influence of the work environment on teacher performance, analyzing the effect of compensation on teacher performance, and analyzing the effect of work professionalism on teacher performance, analyzing the influence of work environment mediated by work professionalism on teacher performance, analyzing the effect of compensation mediated by work professionalism on teacher performance. Design/methodology/approach: The population of this study were teachers of SMA and SMK Kawung 2 Surabaya with a total of 52 teachers. Data analysis using multiple linear regression using SPSS software. Findings: The results showed that work environment has a significant effect on teacher performance, compensation has a significant effect on teacher performance, work professionalism has a significant effect on teacher performance, work professionalism is able to mediate the effect of work environment on teacher performance, and work professionalism is able to mediate the effect of compensation on performance teacher. Paper type: Research paper